Assistência farmacêutica no programa Aqui Tem Farmácia Popular no município de Bauru, SP - Souza, Nency Zaurisio de (2012)
Introduction: The government program called ``Farmácia Popular do Brasil`` was created in order to increase access to essential drugs to patients of chronic diseases in the Brazilian population. Included in this initiative there is another program, the ´´Programa Saúde Não tem Preço`` that favor people to obtain drugs for treatment of hypertension, diabetes, cholesterol alteration and other. Objective: This study sought to study the characteristics of patients with hypertension and / or diabetes in relation to pharmaceutical assistance regarding the`` Programa Aqui tem Farmácia Popular/ Saúde Não tem Preço`` in a pharmaceutical unit in the city of Bauru, identifying customer satisfaction , the average monthly spending with drugs of continuous use before the launch of the program. Method: This is a qualitative and descriptive cross-sectional study, covering a group of 100 users of continued use drugs for chronics diseases related to a pharmaceutical unit of the private network that is part of the mentioned programs in the city of Bauru, SP. Results and Discussion: sociodemographic characteristics of patients studied between the two diseases, hypertension and diabetes, are similar to other national studies available in the literature. In this regards, our results do not deferred in essence to those related to the natural course of chronic diseases. The monthly cost of medications on average was R $ 14.31 for each one of does patients, before joining the free program. Conclusion: The ``Programa Aqui tem Farmácia Popular/ Saúde Não tem Preço is a timely initiative to ensure economic access to users depending on treatment for chronic diseases. The subject deserves attention of health authorities to establish and promote health policies that can slow the effects of these diseases in major population groups, allowing the restriction of the emergence of associated complications and improved the life quality of this group who are affected